2008
DOI: 10.1007/s10461-008-9359-3
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant Injectors in Ukraine: The Next Wave of the Epidemic?

Abstract: This study was designed to assess differences in drug and sex-related risk behaviors between injectors of opiates only, opiate/sedative mix only and stimulants only. Participants were current out-of-treatment injection drug users (IDUs), unaware of their HIV status, recruited through street outreach in Kiev, Odessa and Makeevka/Donetsk, Ukraine. Overall, 22% tested positive for HIV, including 39% among opiate/sedative injectors, 19% among opiate injectors and 17% among stimulant injectors. Despite these differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices. [20][21] A study carried out recently by Otiashvili et al among IDUs in Georgian needle exchange programs found that two thirds of IDUs injected buprenorphine in the past month and approximately a half of these used it to cope with the symptoms of withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices. [20][21] A study carried out recently by Otiashvili et al among IDUs in Georgian needle exchange programs found that two thirds of IDUs injected buprenorphine in the past month and approximately a half of these used it to cope with the symptoms of withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the concurrent use of benzodiazepines, the use of other opiates and home-made stimulants was common in our sample. Even if poly-drug use is a well-known phenomenon in the region and is confirmed by other authors [53,54] , our findings indicate a scenario of even more chaotic drug use in the study sample. The reasons for unsystematic (unstructured) poly-drug use (mixing together buprenorphine with other sedatives and with pseudo/ephedrine-based stimulants at the same time) might be the fluctuating availability of particular substances, the high price of all illegal drugs on the Georgian black market compared to local income levels, and users' attempts to combine different drugs in order to increase the euphoric effects, potency and duration of effect of the preparation.…”
Section: Dosage Of Injected Buprenorphinesupporting
confidence: 86%
“…In 2007, IDUs comprised 60.4% of registered HIV cases [60] . This dangerous situation might be further aggravated by the recent significant increase in the use of home-made stimulants, its frequent concurrent use with buprenorphine [35,37,40] and the existing evidence of increased risky injections and sexual behaviours on the part of amphetamine-type stimulant users [53,54,61,62] . An increase in amphetamine-type stimulant injection in Georgia has been identified in some earlier studies [35,37,41] .…”
Section: Public Health and Illegal Buprenorphine Injecting: The Emergmentioning
confidence: 99%
“…Qualitative research indicates that IDUs inject a variety of mostly homemade drugs using easily accessible over-the-counter ingredients such as cold medicines and household chemicals. Commonly used drugs include the opiate-based ''hanka'' or ''hemia'' (liquid poppy straw or latex involving a lengthy preparation process of mixing chemicals, cooking and straining) and amphetamine-based ''shirka'', ''vint'' or ''jeff'' (ephedrine, methamphetamine, or methcathernone involving a lengthy preparation process of mixing chemicals, cooking and straining) or ''baltushka'' (ephedrine based involving a cold-shaking process to separate tablets from liquid) [8,[10][11][12]. Economic, political and social instability, misinformation and incorrect beliefs about drug injection risks and HIV transmission, social stigmatization, police policies towards IDUs, gender differences in drug use practices are suggested contributors to the rise of HIV among IDUs [8,13].…”
Section: Introductionmentioning
confidence: 99%